Cochlear Nerve Dimensions in Asymetrical Sensorineural Hearing Loss: A Morphometric Study - Ayşe Pelin Yiğider; Ömer Yıldız; Levent Küfeciler; Hasan Emre Koçak; Harun Acıpayam; Fatma Tülin Kayhan; Ercan İnci (İstanbul Medical Journal, 2021)

(untitled)
Introduction:To investigate the relationship between morphometric variants of the cochlear nerve (CN) and the hearing level. To investigate the confounding effects of age, sex, and audiometric variables on the relationship between CN morphometrics and hearing loss, if present.Methods:Audiological data and magnetic resonance imaging findings of 127 patients with asymmetrical sensorineural hearing loss (ASNHL) were reviewed retrospectively. According to pure tone average (PTA) frequencies of each ear, difference above 25 dB were accepted as ASNHL. The vertical (Vd) and horizontal diameters (Hd) and the cross-sectional area (CSA) of the CN were measured.Results:The difference in CSA and Vd between ears showed a negative correlation with age. The mean CSA was 1.57 in AE and 1.60 in NE. Mean Hd was 1.00 in AE and 1.00 NE. Mean Vd was 1.40 in AE and 1.50 in NE. There was no correlation between the difference ratios of thresholds and CN diameter parameters. There was no significant correlation of CSA, Vd, and Hd with PTA thresholds at each frequency.Conclusion:Aging is associated with losses in Vd diameter and CSA. The degree of hearing loss was not correlated with the morphometric features of the CN. The morphometry of the CN should be interpreted together with the etiology of hearing loss.